Criminal Liability of a Notary as a Co-Perpetrator in Embezzlement of Entrusted Funds in Land Transactions - Petra Roni Togar; Agus Surono; Maslihati Nur Hidayati (CV. Social Politic Genius (SIGn), 2026)
This study examines the outer limits of the shift in a Notary’s official responsibility from the administrative sphere to criminal liability for an act beyond authority (ultra vires), namely holding land transaction funds in a personal account through an unauthorized escrow arrangement. This study aims to dogmatically analyze the transformation of procedural malpractice into co-perpetration in embezzlement, examine the proof of trial facts at first instance, and critically evaluate the correction of enforceable custodial sanctions by the High Court and the Supreme Court. This study employs doctrinal legal research using the statute approach, the conceptual approach, and complete legal chain analysis across three judicial levels. The results show that the Defendant’s failure to comply with the protocol requiring the physical presence of appearers in drawing up a power of attorney to sell constituted an act of commission that served as an enabling factor for the commission of the substantive offence. The Defendant’s unilateral control over the settlement funds and fabrication of backdated receipts were qualified as active acts satisfying all elements of embezzlement in the form of co-perpetration (medeplegen). This study concludes that the conditional sentence imposed by the Jombang District Court exceeded the proper limits of judicial discretion. This error was properly corrected by the Surabaya High Court and affirmed by the Supreme Court, which imposed a seven-month enforceable custodial sentence to uphold general deterrence and restore public trust. The policy implication of this study confirms that the Defendant’s dishonourable dismissal from the office of Notary must be pursued through the operation of Article 12 letter c of Law Number 30 of 2004 upon the proposal of the Central Supervisory Council, because the Defendant’s conduct was proven to degrade the dignity of the office.